Forest Fire Hazard Rating Assessment In Peat Swamp Forest Using Integrated Remote Sensing And Geographical Information System - Mohd Razali, Sheriza (2007)
Forest fire can be a real disaster, regardless of their causes, be it human activity or nature. While it is difficult to control nature, it is possible to map different hazard levels thereby minimizing fire hazards and avoid potential damage. Satellite data plays an important role in detecting and mapping forest fires, involving different types of vegetation. This study was conducted with two objectives: first by applying remote sensing techniques to delineate fuel types map and burnt areas in peat swamp forest; secondly was to develop a fire hazard modelling and mapping of fire hazard rating areas using the Geographical Information System (GIS). A fire prone peat swamp forest located in Penor, Pahang was selected for the study. A colour composite image from Landsat Thematic Mapper (TM) was transformed using Tasseled Cap Transformation (TC) and a fuel types map was produced. Roads and canal were digitized and developed as layers using ArcGIS 8.2. These layers were composite and four categories of forest fire hazard ranging from extreme to null were automatically derived. The final forest fire hazard rating map is presented in ArcView 3.1. In conclusion, almost 50% of the study areas were classified as ‘low’ hazard and only 10% of the areas were classified as ‘extreme’ hazard. As a result, the fire hazard map can be used for better forest fire management activities for that area.